Regio- and stereoselective synthesis and evaluation of densely functionalized bispiro[oxindole-isoxazole-indandione] hybrids as anticancer agents. (4th October 2022) - Yin, Zhi-Gang; Liu, Xiong-Wei; Chen, Lin; Liu, Xiong-Li; Pan, Bo-Wen; Zhou, Ying
Abstract : This is the combination of three key pharmacophores through bispiro quaternary carbon atoms and evaluation of their anticancer activity. Abstract : A substrate-dependent, highly β-regioselective one-pot multicomponent 1, 3-dipolar cycloaddition reaction of 3-methyl-4-nitro-5-isatylidenyl-isoxazoles with azomethine ylides (thermally generated in situ from ninhydrin and sarcosine) is reported for the first time, furnishing a library of biologically useful bispiro[oxindole-isoxazole-indandione] hybrids. Target novel and structurally complex compounds have been obtained in good yields and diastereoselectivities (up to 91% yield and 20 : 1 dr) with two adjacent spiro quaternary centres. Furthermore, the described method, which is different from our previous work of α-regioselective cycloaddition of 3-methyl-4-nitro-5-isatylidenyl-isoxazoles, is a highly β-regioselective cycloaddition. The newly synthesized compounds potently inhibited the proliferation of various cancer cell lines. The most potent compound 4ah could induce the apoptosis of K562 cells through a caspase-dependent and -independent pathway.